Age-dependent antioxidant responses to the bioconcentration of microcystin-LR in the mysid crustacean, Neomysis awatschensis. (January 2018) - Min, Byung-Hwa; Ravikumar, Yuvaraj; Lee, Do-Hee; Choi, Kwang Seek; Kim, Bo-Mi; Rhee, Jae-Sung
Abstract: Microcystins (MCs) are naturally occurring algal toxins in the aquatic environment and pose a serious threat to the ecosystem. In general, aquatic populations are structured by organisms of different ages, with varying degrees of biochemical and physiological responses. In this study, juvenile and adult marine mysids ( Neomysis awatschensis ) were exposed to MC-Leucine Arginine (MC-LR) (0.1, 1, and 10 μg L −1 ) for 7 days, and the bioconcentration dynamics and responses of antioxidant defense system were measured during the exposure and additional depuration periods (7 days). MC-LR bioconcentrated in a dose-dependent manner, from a threshold concentration of 1 μg L −1 in both stages, and the levels reduced gradually during the depuration phase. Bioconcentration patterns of MC-LR were highly age-specific, as juvenile mysids showed peaks during the exposure period, whereas adults exhibited a peak on the first day of depuration. After exposure to 10 μg L −1 concentration, elevated levels of malondialdehyde (MDA) and glutathione (GSH) were observed during the late (days 5 and 7) exposure and early (days 1 and 3) depuration periods in juvenile mysids, while adult mysids showed a peak on day 7 of the exposure period. Age-specific responses were also observed in the enzymatic activities of glutathione S -transferase (GST), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione reductase (GR). Juvenile mysids showed a significant elevation in all enzymatic activities during the exposure and/or depuration phase upon exposure to 10 μg L −1 MC-LR, but only CAT and SOD enzymes showed significant changes during the exposure and/or depuration periods in adults. Overall, our results indicate the bioconcentration potential of MC-LR and its threshold in the marine mysid, in addition to age-specific MC-LR dynamics and subsequent biochemical responses. Graphical abstract: Highlights: MC-LR was dose-dependently bioconcentrated from 1 μg L −1 threshold in the marine mysid. Biocencentrated MC-LR concentrations decreased during the depuration phase. MC-LR induced similar dynamics of GSH and MDA at 10 μg L −1 in juvenile and adult mysid. Antioxidant enzyme activities showed age-specific dynamics in the marine mysid. Abstract : Evidence on the age-specific bioconcentration of microcystin in marine mysid and subsequent biochemical responses is extensively studied.